Pediatric Patients in a Local Nepali Emergency Department: Presenting Complaints, Triage and Post-Discharge Mortality - Samita Giri PhD; Tine Halvas-Svendsen MSc; Tormod Rogne PhD; Sanu Krishna Shrestha MD; Henrik Døllner PhD; Erik Solligård PhD; Kari Risnes PhD (SAGE Publishing, 2020)
Background. In low-income countries, pediatric emergency care is largely underdeveloped although child mortality in emergency care is more than twice that of adults, and mortality after discharge is high. Aim. We aimed at describing characteristics, triage categories, and post-discharge mortality in a pediatric emergency population in Nepal. Methods. We prospectively assessed characteristics and triage categories of pediatric patients who entered the emergency department (ED) in a local hospital. Patient households were followed-up by telephone interviews at 90 days. Results. The majority of pediatric emergency patients presented with injuries and infections (~40% each). Girls attended ED less frequent than boys. High triage priority categories (orange and red) were strong indicators for intensive care need and for mortality after discharge. Conclusion. The study supports the use and development of a pediatric triage systems in a low-resource general ED setting. We identify a need for interventions that can reduce mortality after pediatric emergency care. Interventions to reduce pediatric emergency disease burden in this setting should emphasize prevention and effective treatment of infections and injuries.